Evaluation of single reservoir performance for flood risk reduction using a developed simulation model: case study of Makhoul reservoir - Al-Aqeeli, Yousif H.; Abd Aziz, Samsuzana; Yusuf, Badronnisa; Wayayok, Aimrun (Universiti Putra Malaysia Press, 2018)
The objectives of this study were firstly, to develop a simulation model (SM) for a single reservoir to identify the standard operating policy (SOP) of a reservoir based on a monthly operating period, and secondly, to evaluate the performance of the proposed Makhoul reservoir using a Developed Simulation Model (DSM) in reducing flood risk. This reservoir is located on the River Tigris, approximately 180 km upstream of Baghdad, Iraq. The performance of the reservoir in reducing flood risk was evaluated using two designs and records of flood waves gathered over two years. The first design was the present one, while the second was developed by increasing the operational storage to its maximum, based on the digital maps of the region. The flows downstream of the reservoir were compared, with and without the reservoir in the two years in question. Four parameters resulting from the two designs were compared: storage, surface area, elevation and power. The results suggested that the reservoir would be ineffective in reducing flood risk, but it would have the ability to provide hydroelectric power using the two designs, with the new one showing better ability at doing this. The reservoir can also serve purposes such as irrigation, fish wealth development and recreation. This DSM proved its effectiveness in evaluating the performance of the single storage system used for reservoirs.